2010
DOI: 10.1080/15226511003671320
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Arsenic in Submerged Soil by Wetland Plants

Abstract: Wetland aquatic plants including Canna glauca L., Colocasia esculenta L. Schott, Cyperus papyrus L. and Typha angustifolia L. were used in the phytoremediation of submerged soil polluted by arsenic (As). Cyperus papyrus L. was noticed as the largest biomass producer which has arsenic accumulation capacity of 130-172 mg As/kg plant. In terms of arsenic removal rate, however, Colocasia esculenta L. was recognized as the largest and fastest arsenic remover in this study. Its arsenic removal rate was 68 mg As/m2/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Among the submerged aquatic weeds Hydrilla verticillata, Ceratophyllum dermersum, Potamageton crispus, Valisnaria natans, Eleocharis acicularis and Elodea Canadensis widely reported by many researchers to extract As from contaminated water. Studies conducted in laboratory and field conditions indicated that Hydrilla verticillata, and Ceratophyllum demersum can uptake higher proportion of As from contaminated water depending on exposure time and concentration of metalloid [22,56,57]. Unlike Spirodela polyrhiza, Hydrilla verticillata also uptake [50].…”
Section: Phytoremediation By Submerged Aquatic Weedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the submerged aquatic weeds Hydrilla verticillata, Ceratophyllum dermersum, Potamageton crispus, Valisnaria natans, Eleocharis acicularis and Elodea Canadensis widely reported by many researchers to extract As from contaminated water. Studies conducted in laboratory and field conditions indicated that Hydrilla verticillata, and Ceratophyllum demersum can uptake higher proportion of As from contaminated water depending on exposure time and concentration of metalloid [22,56,57]. Unlike Spirodela polyrhiza, Hydrilla verticillata also uptake [50].…”
Section: Phytoremediation By Submerged Aquatic Weedsmentioning
confidence: 99%
“…Unlike Spirodela polyrhiza, Hydrilla verticillata also uptake [50]. Under simulated field condition (aquatic pond) Hydrilla verticillata alone removed sum total 8546 μg (348 μg g −1 ) of As from contaminated water (As concentration 1500 μg L −1 ) which is 72% of the total arsenic supplied [56]. Ceratophyllum demersum reported to accumulate 76 μg g −1 in 4 days and and As accumulation further increased to 201 μg g −1 in 7 days when exposed to 50 μM As solutions [22].…”
Section: Phytoremediation By Submerged Aquatic Weedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructed wetlands (CWs) are designed to take advantage of many of the same processes that occur in natural wetlands, but do so within a more controlled environment (Vymazal 2010). Phytoremediation of constructed wetlands has been used to improve the quality of contaminated waters by acting as a sink for various contaminants discharged from sewage, industrial and agricultural wastewaters, landfill leachate, and storm water runoff (Rai 2008;Jomjun et al 2010;Imfeld et al 2009;Hoffmann et al 2011;Vymazal 2005Vymazal , 2007Sheoran and Sheoran 2006;Brisson and Chazarenc 2009). However, the technology of constructed wetlands for wastewater treatment has not developed to its maximum, and various problems are still present with regard to its best management and sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Canna glauca L., Colocasia esculenta L. Schott, Cyperus papyrus L. and Typha angustifolia L. are recognized as potential plant to eliminate As in wetland ecosystem(Jomjun et al, 2010).There are opportunities to use plants species for remediation agents in Geothermal Power Plant in Lahendong.The area surrounding Lahendong is home for numerous plants which are able to prove as bioaccumulation of As in polluted land and water. However, so far, there are no assessments on the effectiveness of such plants in absorbingthe As.…”
mentioning
confidence: 99%